Partial replacement of Ordinary Portland cement by LCD glass powder in concrete. (2021) - Raju, Akhil S.; Anand, K.B.; Rakesh, P.
Abstract: This paper represents the properties of concrete with partial replacement of cement by LCD glass powder derived from discarded gadgets. This end of life LCD glass powder was obtained from electronic glass scrap and is used in this work after grinding to a particle size of 45 µm or less. X-ray Fluorescence spectroscopy (XRF) test indicates SiO2, Al2 O3, CaO and MgO as the major oxides in the LCD glass powder. The fresh state, hardened state and durability properties of concrete show significant improvement with inclusion of waste LCD glass powder in concrete. 5% replacement of cement by waste LCD glass powder is considered as the optimal replacement level with respect to the strength studies. The compressive strength of 5% replacement is obtained as 20%, 28% and 36% higher than control specimen after 7 days, 28 days and 56 days respectively with regard to chloride ion penetration and sorptivity of concrete, 5% substitution of cement shows optimal results while 20% of partial replacement with LCD glass powder gives the better results on sulphate resistance and acid attack. In concrete, replacement of cement with pozzolanic materials such as waste LCD glass powder may be a viable option in mitigating environmental pollution through a reduction in cement consumption as well as by accommodating solid waste.